Sex differences in mortality after abdominal aortic aneurysm repair in the UK. Issue 12 (26th July 2017) - Sidloff, D A; Saratzis, A; Sweeting, M J; Michaels, J; Powell, J T; Thompson, S G; Bown, M J
Abstract: Background: The UK abdominal aortic aneurysm (AAA) screening programmes currently invite only men for screening because the benefit in women is uncertain. Perioperative risk is critical in determining the effectiveness of screening, and contemporary estimates of these risks in women are lacking. The aim of this study was to compare mortality following AAA repair between women and men in the UK. Methods: Anonymized data from the UK National Vascular Registry (NVR) for patients undergoing AAA repair (January 2010 to December 2014) were analysed. Co-variables were extracted for analysis by sex. The primary outcome measure was in-hospital mortality. Secondary outcome measures included mortality by 5-year age groups and duration of hospital stay. Logistic regression was performed to adjust for age, calendar time, AAA diameter and smoking status. NVR-based outcomes were checked against Hospital Episode Statistics (HES) data. Results: A total of 23 245 patients were included (13·0 per cent women). Proportionally, more women than men underwent open repair. For elective open AAA repair, the in-hospital mortality rate was 6·9 per cent in women and 4·0 per cent in men (odds ratio (OR) 1·48, 95 per cent c.i. 1·08 to 2·02; P = 0·014), whereas for elective endovascular AAA repair it was 1·8 per cent in women and 0·7 per cent in men (OR 2·86, 1·72 to 4·74; P < 0·001); the results in HES were similar. For ruptured AAA, there was no sex difference in mortality within the NVR; however, in HES, for ruptured open AAA repair, the in-hospital mortality rate was higher in women (33·6 versus 27·1 per cent; OR 1·36, 1·16 to 1·59; P < 0·001). Conclusion: Women have a higher in-hospital mortality rate than men after elective AAA repair even after adjustment. This higher mortality may have an impact on the benefit offered by any screening programme offered to women. Abstract : Mortality double in women